Aspects of the morphology, parasite host specificity and genetics of selected Labeobarbus polylepis populations - Austin, Amanda (2011)
M.Sc. === The Bushveld smallscale yellowfish, Labeobarbus polylepis (Boulenger, 1907), is an ecologically, socially and economically important species. These indigenous freshwater fish are found above an altitude of 600m, and occur in the Inkomati and Phongolo River Systems and the southern tributaries of the Limpopo River System. In the past, it was suspected that morphological differences exist between the different L. polylepis populations, due to the occurrence of the rubberlip formation of individuals from the Elands River. Specimens of five L. polylepis populations were collected from the Phongolo, Assegaai, Elands and Komati rivers and Ngodwana Dam, Mpumalanga, South Africa. A L. natalensis population was collected from the Umvoti River and used as an out-group. Nine meristic counts and 46 morphometric measurements were taken. The measurements were changed into percentage ratios based on the fork length of each individual. The data was statically analysed and includes Multidimensional scaling techniques (MSD’s) and Principle Component Analysis (PCA’s). Statistical analysis split the five populations into three groups. The one group consists of fish from the Phongolo and Assegaai rivers, the second group consists of fish from the Elands River and Ngodwana Dam and the third group is mainly Komati River fish. The third group is the only group that does not overlap with any other group. There were morphological differences between the groups, but they were not significant. The L. natalensis population is morphologically similar to L. polylepis populations obtained from the Phongolo and Assegaai rivers. Twenty enzyme coding loci in two L. polylepis populations from the Phongolo and Elands rivers were analysed by horizontal starch gel-electrophoresis. Electrophoretic analysis of heart, muscle and liver tissue samples revealed genetic variation at 15% (Elands River) and 35% (Phongolo River) of the protein coding loci studied. Average heterozygosity values based on Hardy-Weinberg expectation were 0.019 (Elands River) and 0.059 (Phongolo River), with a genetic distance value of 0.004 between these populations.